2020
DOI: 10.1097/cce.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Implementation Science in Adult Critical Care Settings

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 101 publications
0
18
0
Order By: Relevance
“…Another scoping review for evidence-based practices in critical care in general also found considerable variability in the nomenclature that was used to describe implementation strategies. 85 Standardised and transparent reporting is recommended to compare the effectiveness of certain strategies. 83 86 Corresponding to our critical appraisal, previous reviews also found that most evidence on ICU bundle effects has weak methodological quality.…”
Section: Discussionmentioning
confidence: 99%
“…Another scoping review for evidence-based practices in critical care in general also found considerable variability in the nomenclature that was used to describe implementation strategies. 85 Standardised and transparent reporting is recommended to compare the effectiveness of certain strategies. 83 86 Corresponding to our critical appraisal, previous reviews also found that most evidence on ICU bundle effects has weak methodological quality.…”
Section: Discussionmentioning
confidence: 99%
“…33 There is a need to implement, at all times, care based on the latest scientific evidence. 33 This improved care must be approached from the set of needs detected by nurses and noted in our findings. This first approach in the Spanish health system environment has given us the possibility of detecting similarities with previous factor analyses in other health environments.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation science seeks to identify, optimize, and accelerate research into practice 17 . It can be used in healthcare to identify barriers and facilitators, develop interventions to overcome barriers, and translate research into the clinical setting 18 .…”
Section: Framework and Methodsmentioning
confidence: 99%